The Bactericidal Efficacy and the Mechanism of Action of Slightly Acidic Electrolyzed Water on Listeria monocytogenes’ Survival - Huiying Li; Duo Liang; Jin Huang; Chaojing Cui; Huan Rao; Dandan Zhao; Jianxiong Hao (Foods, 2021)
In the present work, the bactericidal efficacy and mechanism of slightly acidic electrolyzed water (SAEW) on L. monocytogenes were evaluated. The results showed that the strains of L. monocytogenes were killed completely within 30 s by SAEW whose available chlorine concentration (ACC) was higher than 12 mg/L, and it was confirmed that ACC is the main factor affecting the disinfection efficacy of SAEW. Moreover, our results demonstrated that SAEW could destroy the cell membrane of L. monocytogenes, which was observed by SEM and FT-IR, thus resulting in the leakage of intracellular substances including electrolyte, protein and nucleic acid, and DNA damage. On the other hand, the results found that SAEW could disrupt the intracellular ROS balance of L. monocytogenes by inhibiting the antioxidant enzyme activity, thus promoting the death of L. monocytogenes. In conclusion, the bactericidal mechanism of SAEW on L. monocytogenes was explained from two aspects including the damage of the cell membrane and the breaking of ROS balance.